A Review of Mathematical Models of COVID-19 Transmission (Contemporary Mathematics, 2023)
Corona Virus Disease 2019 (COVID-19) is a disease caused by the novel coronavirus, and due to its rapid spread, the World Health Organization has declared it a worldwide outbreak. Since the first case was detected in December 2019, the fight against this deadly disease has begun. Numerous studies have been done on the COVID-19 outbreak's model of dissemination and epidemic patterns. It mainly focuses on the selection of methods, the determination of parameters, and the evaluation of prevention and control measures. Taking the spread of the COVID-19 epidemic as the research object, combined with the current development of the COVID-19 epidemic, this paper sorts out the relevant mathematical models for the study of the spread of COVID-19, among which the models based on Susceptible-Infected-Recovered (SIR) model and Susceptible-Exposed-Infectious-Removed (SEIR) model and the mathematical models combined with these two models are mainly selected. Finally, the importance of reasonable and effective control of parameters and multi-model combined modeling is pointed out in the future.
Keywords: COVID-19, epidemiology, mathematical model